2021
DOI: 10.1016/j.imu.2021.100714
|View full text |Cite
|
Sign up to set email alerts
|

A computational study on hydroxychloroquine binding to target proteins related to SARS-COV-2 infection

Abstract: COVID-19 disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has posed a global health emergency. Repurposing of existing drugs can be a rapid and effective strategy to fight the infection. Clinical trials have reported reduction or elimination of viral load when patients were treated with the anti-malarial drug Hydroxychloroquine (HCQ). To understand the molecular mechanism of action for effective repurposing of this drug we have carried out in silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 70 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…[41][42][43] This finding was consistent PubChem, provided valuable insights into the binding interaction between the HCQ/SM mixture and its affinity toward HSA. [15,[44][45][46][47][48][49][50] 2.6 | Molecular docking with SARS-CoV-2 virus as a receptor (PDB ID: 6LU7 and 7TLL) protein…”
Section: Molecular Docking With Hsa Protein As a Receptor (Pdb: Id: 5...mentioning
confidence: 99%
See 2 more Smart Citations
“…[41][42][43] This finding was consistent PubChem, provided valuable insights into the binding interaction between the HCQ/SM mixture and its affinity toward HSA. [15,[44][45][46][47][48][49][50] 2.6 | Molecular docking with SARS-CoV-2 virus as a receptor (PDB ID: 6LU7 and 7TLL) protein…”
Section: Molecular Docking With Hsa Protein As a Receptor (Pdb: Id: 5...mentioning
confidence: 99%
“…The individual molecules are found to be within the hydrogen bonding range of Trp 214 residue subdomains IB, IIA, and IIIA, according to docking experiments. [14] Also, Lan-Yi Hu and collaborators reported the affinity behavior of chloroquine and HCQ with HSA using computer simulation and the multispectral approach of biochemistry [5,15] Several drugs, including remdesivir, favipiravir, dexamethasone, and HCQ, have exhibited therapeutic efficacy in early clinical treatment of patients with COVID-19. These medications have demonstrated the ability to rapidly reduce viral load using various mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of spike-ACE2 attachment by binding an NMA at a site other than the ACE2 active site is a promising strategy to design novel drugs for COVID-19 treatment because when an NMA binds to spike protein fragments, a conformational change occurs and modifies the binding energy of ACE2 and spike protein complexes. Finally, the binding structure of ACE2 and spike protein fragments becomes unstable [ 49 , 50 ] ( Fig. 2 ).…”
Section: Compounds Affecting Spike–ace2 Complexmentioning
confidence: 99%
“…Interestingly, in silico docking and dynamics studies have recently identified ACE2 receptor as well as novel HCQ targets including the α7 nicotinic AcetylCholine Receptor (α7 nAChR), α1D-adrenergic receptor (α1D-AR), Histamine N-Methyl Transferase (HNMT) and DNA gyrase/Topoisomerase III β (Top3β) [ 64 ]. In particular, the authors found that HCQ would block virus-binding sites on both ACE2 and α7 nAChR at the entry stage, whereas at post-entry stages, HCQ would prevent viral replication by acting against Top3β, and the “cytokine storm” by inhibiting α1D-AR.…”
Section: Antimalarial Drugsmentioning
confidence: 99%